2011
DOI: 10.1080/21513732.2011.603138
|View full text |Cite
|
Sign up to set email alerts
|

The Niger Delta wetlands: threats to ecosystem services, their importance to dependent communities and possible management measures

Abstract: The Niger Delta wetlands are changing rapidly, raising concern for the wetlands' health and for communities relying upon its ecosystem services. Knowledge on ecosystem service provision is important for effective ecosystem and livelihoods management, but is currently lacking for the Niger Delta. We synthesised literature and used the 'Drivers-pressure-state-impact-response' (DPSIR) framework to structure information on changes in the wetlands' ecosystem services and implications for dependent communities. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(43 citation statements)
references
References 107 publications
2
29
0
Order By: Relevance
“…Inadequate institutional arrangements are often regarded as drivers of environmental change [55]. Our results support those studies emphasizing the political and institutional factors involved in the degradation of ecosystems, [13,43]. A holistic management plan for the wetlands with participatory options and approaches and multisectoral investment might help communities to reduce their high dependency on wetland resources, which ultimately should result in increases in the flow of ecosystem services.…”
Section: Discussionsupporting
confidence: 79%
“…Inadequate institutional arrangements are often regarded as drivers of environmental change [55]. Our results support those studies emphasizing the political and institutional factors involved in the degradation of ecosystems, [13,43]. A holistic management plan for the wetlands with participatory options and approaches and multisectoral investment might help communities to reduce their high dependency on wetland resources, which ultimately should result in increases in the flow of ecosystem services.…”
Section: Discussionsupporting
confidence: 79%
“…We did not value provisioning service such as the water supply potentials of the Niger Delta wetlands because water does not generally have a market value in this society. The Niger Delta wetlands provide an array of provisioning, regulating, cultural and supporting services which are of global importance, but more importantly rural livelihoods (Adekola and Mitchell 2011). Like previous studies of African wetlands, we confirmed the high importance of provisioning ecosystem services in households.…”
Section: Discussionsupporting
confidence: 76%
“…The main consequences of local community activities include changes in soil productivity and decline in forest cover (Adekola and Mitchell 2011). It has not been possible to estimate this cost because of a lack of reliable data.…”
Section: Costs Associated With Local Community Activitiesmentioning
confidence: 99%
“…In this regard, the supply of services by specific or mosaic of land covers must be taken into account (Burkhard et al, 2010) for planning and management of the areas of concern. However, information on land covers, its capacity to supply services and the consequences of land cover change on ecosystem services at a local scale is largely absent (Adekola and Mitchell, 2011). Information on people's dependency on natural resources at local scale is also limited though half of the world's rural population is estimated to depend on natural resources for subsistence products or cash income generation (Angelsen and Wunder, 2003).…”
Section: Introductionmentioning
confidence: 99%